SUICIDE AND PSYCHOLOGICAL FACTORS IN HISTORICAL PROCESS AND THEORETICAL PERSPECTIVE - YENER ÖZEN; NIMET ÖZEN; TAHA BERKAY BÖREKÇI; UTKU CAN; EMRAH GERÇEK (Innovare Journal of Social Sciences, 2025)
Suicide is a complex phenomenon that goes deep into human history and has gained different meanings and been evaluated in different societies, cultures, and periods. It has been observed that throughout the historical process, suicide has been shaped by many factors such as social norms, religious beliefs, psychological factors, and legal approaches. When considered from a perspective extending from ancient times to the present day, the perception and evaluation of suicide have undergone significant evolutions. While suicide was considered a sign of dishonor in ancient societies, during the Renaissance, it was romanticized as a reflection of the individual’s freedom and emotional expression. In the modern period, factors such as psychiatric perspectives, public health strategies, and international cooperation have played a critical role in understanding and preventing suicide. This study aims to examine the evolution of humanity’s efforts to cope with this challenging problem by addressing the history of suicide in various cultural and periodic contexts.